Analisis Laporan Keuangan BCA Syariah - Natalia Natalia; Juli Anggraini; Daffa Salsabilla Sanjaya; Aulia Davita; Hisyam Fadhlurrahman; Endy Putra (BADAN PENERBIT STIEPARI PRESS, 2024)
Banks are really needed by society when they want to progress and develop. Various types of financial activities are carried out by banks as a form of financial institution that can be trusted by the wider community. With the aim of obtaining maximum profits, Islamic banks adhere to sharia principles in asset management and maintain customer trust in the form of accountability in fulfilling their obligations as an organization that relies heavily on the principle of trust. In this case, financial support will be provided by Bank BCA Syariah through a profit sharing program.